Tradisi Pengobatan Moalo Sanggoleo pada Suku Tolaki di Kelurahan Petoaha Kecamatan Nambo Kota Kendari - Irawati Tapasi; Adelina Mahmuddin; Abdul Alim; Nurtikawati Nurtikawati (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
The Moalo Sanggoleo healing tradition is a treatment process carried out on someone who is caused by hearing and seeing something that makes the person feel bad and feel afraid. This research aims to 1) find out and explain the process of implementing the Moalo Sanggoleo healing tradition among the Tolaki tribe in Petoaha Village, Nambo District, Kendari City. 2) find out and explain the meaning of the speech contained in the Moalo Sanggoleo healing tradition among the Tolaki tribe in Petoaha Village, Nambo District, Kendari City. In this research, Roland Barthes' semiotic theory is used, the type of research is descriptive qualitative, with data collection techniques carried out by observation, interviews and documentation, then analyzed by data reduction, data presentation and data verification. The results of this research show that the process of implementing the Moalo Sanggoleo tradition consists of several stages, namely the stage of determining the time and place for the treatment, the parties involved in implementing the treatment, the stage of implementing the treatment which consists of diagnosing the disease and the process of implementing the Moalo Sanggoleo treatment and the healing stage. The meaning of the speech contained in the Moalo Sanggoleo treatment is found in the mantra used in the Moalo Sanggoleo treatment process, namely the Moalo Sanggoleo treatment mantra nad the bathring water mantra which have denotative and connotative meaning.